Lifestyle and Socioeconomic Transition and Health Consequences of Breast Cancer in the East Asia Region, From 1990 to 2019 - Mubarik, Sumaira; Cao, Jinhong; Wang, Fang; Hussain, Syeda Rija; Liu, Qing; Wang, Suqing; Liu, Yan; Yu, Chuanhua (Frontiers in Nutrition, 2022)
Background: Due to its higher prevalence and heterogeneity, female breast cancer (BC) is the most widely disease throughout the world. We sought to assess the epidemiological and sociodemographic transitions of BC and to identify the potential risk factors attributed to BC-burden in East-Asia. Methods: At the regional level of East-Asia and at a national level of East-Asian countries, we investigated the burden of female BC incidence, mortality, and DALYs in 2019 and assessed the epidemiological, socioeconomic and health linked disparities in BC’s incidence and mortality over a 30-year period. The changes in BC’s mortality and DALYs between 1990 and 2019, attributable to varying risk factors, were evaluated in different age groups. Results: In 2019, the incidence of, mortality from and DALYs of BC were estimated to be 382,321 (95% UI: 303,308-477,173) incidence cases (age-standardized rate (ASR) of 35.69 per 100k; 28.32–44.54), 98,162 (79,216-120,112) deaths (ASR of 9.12; 7.36-11.13), and 3,024,987 (2,477, 984-3,659,370) DALYs with an ASR of 282.15 (230.81-341.19) in 2019. It was also observed that out of four most representative location of East Asia two (China and Japan) showed the greater than 60% change in incidence between 1990 and 2019. While only Japan females showed the significant rise of 15.3% (95% UI: 2.3-28) in ASR of death, and 12.6% (95% UI: 0.5-26.9) in ASR of DALYs between 1990 and 2019. Inclusive, 88% and 81% variation were explained in BC incidence and death due to change in social demographic index (SDI) in 2019, in East Asia. The highest positive percent change in death and DALYs between 1990 and 2019 were attributable to high body mass index (BMI), high fasting plasma glucose (FPG), and alcohol consumption in East Asia. Conclusions: The burden of death and disability from female BC is the result of multiple risk factors, mainly due to behavioral and metabolic risk factors. The increase of the incidence is related to the westernized lifestyle and diet habits and the improvement of screening and diagnosis techniques in recent years, while the increase in DALYs is mainly attributed to high BMI, high FPG, Alcohol use and diet high in red meat.